Measurement properties of the EuroQoL EQ-5D-5L to assess quality of life in patients undergoing carpal tunnel release. (November 2016) - Marti, C.; Hensler, S.; Herren, D. B.; Niedermann, K.; Marks, M.
The objective of this study was to investigate the measurement properties of the EuroQol EQ-5D-5L questionnaire (EQ-5D-5L). A total of 60 patients with carpal tunnel syndrome completed the EQ-5D-5L twice before surgical decompression and once more 6 weeks after surgery. In addition, they filled out the Short Form 12 and Michigan Hand Outcomes Questionnaire at the baseline and postoperative follow-up examinations. Test–retest reliability was excellent with an intraclass correlation coefficient of 0.81. Internal consistency was high with Cronbach's alpha of 0.83. Good validity of the EQ-5D-5L was indicated by correlations of r  = 0.7 and r  = 0.5 with the Short Form 12 and Michigan Hand Outcomes Questionnaire, respectively. Moderate responsiveness was shown by an effect size of 0.5. The minimal important change was 0.09 points. Overall, the EQ-5D-5L demonstrates sound measurement properties and can be recommended as a suitable tool to assess quality of life in patients with carpal tunnel syndrome. Level of evidence: I